Factors Affecting the Affective Identity-Motivation to Lead (AI-MTL) of Lecturers: Case Study in X Unversity - Yosua, Immanuel; Panggabean, Hana (Faculty of Psychology, Diponegoro University, 2021)
This study aims to explore the effect of Leadership Self-Efficacy (LSE), Past Leadership Experience (PLE),Organizational Identification (OI), and Perceived Job Stress as an Academic Leader (PJSAL) on AffectiveIdentity-Motivation to Lead (AI-MTL) of lecturers at the X University simultaneously. This study also aims toexplore the role of LSE in mediating relationship between PLE and AI-MTL as well as between PJSAL and AI-MTL. A total of 125 X University lecturers participated in this study (male: 53, female: 72; age range between26-71 years old), with data collected through an online questionnaire. Data analysis then was performed using theHierarchical Multiple Regression and Mediation Analysis. The result shows that there is a simultaneous effect ofLSE, PLE, OI, and PJSAL, in predicting AI-MTL of lecturers at the X University, F(4, 120) = 63.520, p < .001.All variables can explain 67.9% of the AI-MTL variation, R2 = .679. Meanwhile, PJSAL does not provide anymeaningful contribution to the AI-MTL variation. In addition, this study also confirms the role of LSE inmediating the relationship between PLE and AI-MTL partially, c’ = 1.0508, p < .001, and fully mediating therelationship between PJSAL and AI-MTL, c’ = -.006, p > .05. These results emphasize the strong need to identifytalents by using those factors, especially when universities have difficulty in finding their prospective leaders.